Modelling, Simulation, and Implementation of Effective Controller for KY Stepping Up Converter. (11th January 2022) - Kumar, K. Ramash; Anandhi, T. S.; Vijayakrishna, B.; Balakumar, S.
Abstract : This paper studies on a new Hybrid Posicast Control (HPC) for Fundamental KY Boost Converter (FKYBC) worked in Continuous Current Mode (CCM). Posicast is a feed-forward compensator. It reduces the overshoot in the step result of the flippantly damped plant. But the conventional controller approach is sensitive owing to the changes in the natural frequency. So, as to reduce this undesirable sensitivity and load potential control of FKYBC, a HPC is designed in this article. Structure of HPC is posicast with feedback loop. The independent computational time delay is the main design function of the posicast. The enactment of the FKYBC with HPC is confirmed at various operating regions by making the MATLAB/Simulink and experimental model. The posicast function values are implemented in Arduino Uno-ATmega328P microcontroller. The results of new HPC have produced minimal noise in control signal in comparison with traditional PID control.